2020
DOI: 10.1126/sciadv.aay2669
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoregulation of Rad51/Rad52 by CDK1 functions as a molecular switch for cell cycle–specific activation of homologous recombination

Abstract: Homologous recombination is exquisitely activated only during specific cell phases. In the G1 phase, homologous recombination activity is completely suppressed. According to previous reports, the activation of homologous recombination during specific cell phases depends on the kinase activity of cyclin-dependent kinase 1 (CDK1). However, the precise regulatory mechanism and target substrates of CDK1 for this regulation have not been completely determined. Here, we report that the budding yeast CDK1, Cdc28, pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…However, RPA presents a barrier to RAD51 filament assembly [109,143]. During S/G2, RAD51 is phosphorylated by CDK1, which enhances its ability to compete with RPA for ssDNA [144]. However, RAD51 alone cannot efficiently replace RPA from ssDNA in vivo [143].…”
Section: Rad51 Filament Formationmentioning
confidence: 99%
“…However, RPA presents a barrier to RAD51 filament assembly [109,143]. During S/G2, RAD51 is phosphorylated by CDK1, which enhances its ability to compete with RPA for ssDNA [144]. However, RAD51 alone cannot efficiently replace RPA from ssDNA in vivo [143].…”
Section: Rad51 Filament Formationmentioning
confidence: 99%
“…Three protein kinases (Mec1 ATR , Tel1 ATM and Cdc28 cdk ) are known to phosphorylate budding yeast Rad51 at different target sites (Table 1 ) (Flott et al 2011 ; Lim et al 2020 ; Woo et al 2020 ). Cdc28 cdk , the catalytic subunit of cyclin-dependent protein kinase (CDK), is the master regulator of mitotic and meiotic cell cycles in S. cerevisiae .…”
Section: Human and Yeast Rad51 Recombinases Are Differentially Phosphorylated By Multiple Protein Kinasesmentioning
confidence: 99%
“…Using a monoclonal antibody specific for phospho-serines (S*) in PXS*P, PXS*PXR/K or S*PXR/K motifs, it was found that Cdc28 cdk could phosphorylate S 125 and S 375 of an epitope-tagged Rad51 (HA-TEV-Rad51) both in vitro and in vivo (Table 1 ). Yeast mutant analyses further revealed that mutant non-phosphorylatable Rad51-2A (i.e., Rad51-S 125 A, S 375 A) and Rad51-2E (i.e., Rad51-S 125 E, S 375 E) impair the DNA binding affinity of Rad51 and the Rad51–Rad52 interaction (Lim et al 2020 ). Although these results are important, it is noteworthy that the addition of an epitope or fusion protein tag(s) to native Rad51 often results in deleterious impacts to its normal cellular function and/or unexpected post-translational modification(s) (CNC and TFW, unpublished results).…”
Section: Human and Yeast Rad51 Recombinases Are Differentially Phosphorylated By Multiple Protein Kinasesmentioning
confidence: 99%
“…In response to DNA damage, ATM self-phosphorylates and becomes an active monomer that phosphorylates a wide array of target proteins involved in cell cycle checkpoints and DNA repair, such as cyclins, cyclin-dependent kinases, and transcriptional factors such as SOG1 (Kurzbauer et al, 2021;Yoshiyama et al 2014). In turn, SOG1 targets genes such as the classical tumor-suppressor gene BREAST CANCER SUSCEPTIBILITY GENE 1 (BRCA1) and the recombinase gene RADIATION SENSITIVE 51 (RAD51) which are required for a) enforcement of the G1/S and G2/M cell-cycle checkpoints and b) for high-fidelity homologous recombination, but may also target Lupus Ku autoantigen protein p80 (KU80) and DNA Ligase 4 (LIG4) which are required for low-fidelity Non-Homologous End Joining (NHEJ) (Dorn et al, 2019;Pfeffer et al, 2017;Schröpfer et al 2014;Yoshiyama et al 2014, Lim et al, 2020. Taken together these results suggest that the putative sequences for gene ATM (i.e., ZeaATM1 in maize) in Costa Rican purple landraces P1 and P2, and genes SOG1, RAD51 and BRCA1 (i.e., ZeaSOG1, ZeaRAD51 and ZeaBRCA1) in landrace P1 might feature polymorphisms that presumably promote homology-dependent DNA repair.…”
Section: Resultsmentioning
confidence: 99%